Understanding of Nutritional Practices and Dietary Patterns Among Adolescents Experiencing Iron Deficiency Anemia - Sulastini; Perceka, Andhika Lungguh; Suliyawati, Eti (International Journal of Integrative Sciences, 2024)
Teenage girls constitute a demographic vulnerable to anemia, a condition crucial for shaping the future generation, characterized by a deficiency in both the quantity and size of red blood cells. This study aims to investigate potential correlations between adolescents' understanding of nutrition, their dietary intake, and the prevalence of anemia among girls at SMAN 6 Garut. This type of research is typically categorized as descriptive correlation, which aims to determine the description of dietary knowledge in patients with iron deficiency anemia at SMUN 6 Garut Regency. the sample size consisted of 20 respondents.   Data collection methods are by using questionnaires through direct interviews and the utilization of Easy Touch measuring instruments to assess Hb levels. The findings indicated that the description of knowledge about nutrition in adolescents with iron deficiency anemia in Smun 6 Garut Regency was found to have mostly sufficient knowledge. Most of the adolescents with iron deficiency anemia in SMAN 6 Garut Regency had a bad diet. Parents play a significant role in food selection for their families, while teachers also play a crucial part in monitoring their students' health